Pengembangan E-Modul Berbasis Learning Content Development System Pokok Bahasan Pola Bilangan SMP - Ula, Iin Rahmatul; Fadila, Abi (Desimal: Jurnal Matematika, 2018)
This study aims to produce instructional materials in the form of electronic module based learning content development system on the matter of pattern number. This research method is Research and Development (R & D) based on ADDIE model. Assessment of material experts on the learning media is included in the category of "Valid" with an average value of 3.46. The media expert's assessment of this e-module is included in the "Valid" category with an average grade of 3.66. The linguist's assessment of this medium is included in the "Valid" category with an average grade of 3.6. In a small-scale trial followed by 10 students of class VII obtained an average score of 3.65 based on the results of a response questionnaire that has been filled by the learner, this result puts the e-module on the criteria "Very Interesting". In large-scale field trials followed by 30 students, the average score of attractiveness obtained was 3.55 on the criteria "Very interesting".